Evaluation of biological control strategies for polyphagotarsonemus latus (banks) and phyllocoptruta oleivora (ashmead) on valencia orange (2012)
The damage caused by P. latus and P. oleivora mites in the orange crop Valencia (Citrus sinensis L.) has an economical detrimental impact due to the external damage of the fruits. To evaluate the effect of biological control agents for these two pests, this work was carried out in a commercial crop in Caicedonia, Valle del Cauca, Colombia. The experimental design consisted of a randomized complete block, in which the following treatments were evaluated: (1) release of Phytoseiidae native species: Neoseiulus anonymus, Neoseiulus californicus, Iphiseiodes zuluagai and Amblyseius herbicolus (500 individuals / tree); (2) release of Chrysoperla carnea larvae (100 larvae/tree); (3) exclusion of beneficial agents (localized application of cypermethrin 2 cm3/l) and (4) farmer control (localized application of abamectin, 1.5 cm3/l). The releases and applications of the treatments were made on marked floral clusters and fruits in the middle third of each tree. Evaluations were made weekly until harvest time. For management of P. latus it was found that the treatments Phytoseiidae release, C. carnea release and abamectin application showed the least damage; exclusion of the beneficial agents demonstrated the importance of the natural control agents on this pest. For management of P. oleivora, C. carnea release and abamectin application showed the least damage. In release treatments of Phytoseiidae native species and the exclusion of beneficial agents, P. oleivora caused significant damage.